Administración y gestión logística de la Unidad de Gestión Educativa Local Ucayali - Contamana 2021 - Torrejón Villacorta, Luis Abraham (2023)
The general objective of the research was to determine the relationship between the administration and logistics management of UGEL Ucayali - Contamana, 2021. Establishing itself as an applied study, descriptive and correlation level, non-experimental design, for which a sample has been taken out of 40 workers, the survey technique and the questionnaire were chosen as the instrument for data collection. Therefore, the work concluded that the relationship between administration and logistics management is significant and considerable, since it has been contrasted by a significance of 0.000 and a correlation r of 0.813. Likewise, administration is related to storage, contrasted by a significance of 0.000 and a Pearson correlation at a mean level of 0.586. At the same time, administration is significantly related to material handling, since a correlation coefficient of 0.800 has been calculated. Likewise, the administration is related to the purchasing process, which was contrasted by a correlation coefficient of 0.749. Finally, the administration is significantly related to the maintenance of the information, a relationship that was contrasted by a coefficient at the average level of 0.571.